Analisis Potensi Bahaya dan Risiko di Gudang Bahan Berbahaya dan Beracun (B3) RSUD Blambangan - Dita Amanda Deviani; Anung Kustriyani; Budi Tantri Anisa Lestari (PROFESSIONAL HEALTH JOURNAL, 2024)
Potential hazards are things that have the potential to cause incidents resulting in losses. Besides the risk of disease infection, hospitals have other hazards, such as Hazardous and Toxic Materials. Hazardous and Toxic Materials refer to chemical and biological substances, either individually or mixed, which contaminate and disrupt the environment due to their properties, concentration, or quantity and endanger the health of all contaminated organisms. Blambangan Regional Public Hospital is a workplace with potential hazards and risks that can lead to work accidents. This study aimed to identify potential hazards and risks in the Hazardous and Toxic Materials Warehouse at Blambangan Regional Public Hospital. This research was a qualitative descriptive study with an observational approach using the Job Safety Analysis (JSA) method. The research was conducted at the Hazardous and Toxic Materials Warehouse at Blambangan Regional Public Hospital in June-July 2023. The results identified medium-risk potential hazards and risks in the Hazardous and Toxic Materials Warehouse at Blambangan Regional Public Hospital: moving and arranging goods from trolleys to storage pallets, delivering B3 materials to Hemodialysis Units, an unclean environment in the Hazardous and Toxic Materials warehouse, scattered cardboard boxes piles. If muscles are subjected to repeated loads over a long period, there is a risk of joint damage (musculoskeletal disorders). This research concludes that potential hazards exist in Blambangan Regional Public Hospital's Hazardous and Toxic Materials warehouse located in Banyuwangi, including ergonomic, chemical, and mechanical dangers, each with a medium risk ranking.